Experimental study and application of dolomite aeration oxidation filter bed for the treatment of acid mine drainage. (1st October 2020) - Chai, Youzheng; Qin, Pufeng; Zhang, Jiachao; Wu, Zhibin; Li, Tianyou; Xu, Wenbin; Sun, Haibo
Graphical abstract: Highlights: Dolomite aeration oxidation filter bed combined process for AMD treatment was studied. The effect of key parameters on treatment efficiency and pH adjustment was studied. System has longer service life, lower cost, and smaller residual contamination. The application and economic benefits of this process in practical projects was evaluated. Abstract: Water pollution from acid mine drainage (AMD) has received extensive attention in recent years. However, previously used active treatment methods have many problems, such as high cost, difficult maintenance, and a large amount of sludge production. This study presented a novel process that combined dolomite aeration and an oxidation filter bed. The acidic water generated from coal mine drainage water was the object of research. First, the effects of important operating factors (such as particle size, initial pH, aeration rate, and flow rate) to neutralize acidity and remove contaminants from real mine effluents were studied. Based on these results, the treatment efficiency and sludge performance under repeated treatment were compared between the dolomite and limestone processes. Then the treatment effect under recycling condition was also compared between dolomite and limestone processes. Finally, the application and economic benefits of this combined process in the practical treatment project were evaluated. It was revealed that the Fe(II), total Fe removal efficiency all could reach nearly 100%, and the sulfate removal efficiency and pH could reach 96.2% and 6.53, respectively, after 3 h reaction under optimal conditions (dolomite particle size 0.5–1 cm, initial pH 4, aeration rate 10 L/min, flow rate 100 mL/min). The comparison results show that the dolomite process could achieve good effects while the neutralization agent consumption rate was at least 3 times slower than limestone. Meanwhile, the effluent quality was stable, and the sludge quantity was only one-third that of the sludge quantity produced from the limestone process. The setting capacities of sludge in the dolomite process were better than the limestone process. Additionally, the consumption of dolomite was better than that of limestone. The findings indicated that important cost reduction could be realized by substituting the limestone process with the dolomite aeration oxidation filter bed process, and has good performance in the engineering application.